Stereoselective Total Syntheses of (−)‐Flueggine A and (+)‐Virosaine B1. Issue 2 (21st November 2012) - Wei, Hao; Qiao, Chuang; Liu, Gang; Yang, Zhen; Li, Chuang‐chuang
<x xml:space="preserve">Abstract</x> Convergent approach: The total syntheses of (−)‐flueggine A and (+)‐virosaine B (see scheme) have been accomplished in a concise and convergent manner. Key steps in these approaches were relay ring‐closing metathesis reactions for rapid construction of the key intermediates, and 1, 3‐dipolar cycloaddition reactions for the formation of the natural products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>